Community participation in the utilization of Mansinam Island as an ecotourism object - Komber, Lusia Ludibina Sarce; Situmoran, Elina R.; Aninam, Johny; Wurarah, Rully Novie (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
As an ecotourism attraction in Manokwari Regency, West Papua Province, Mansinam Island offers a unique combination of natural beauty, historical sites, and religious values. However, it still faces challenges such as attraction diversity and lack of infrastructure. This study aimed to understand the interaction of the local community with aspects of ecotourism, including environmental preservation, economic development, and socio-culture. Using interview and questionnaire methods, this study collected data from 38 respondents purposively selected from the residents of Mansinam Island. Data analysis was conducted through a tabulation process to identify three main variables: the role of the community in economic, environmental, and social activities related to ecotourism. The results showed that, although Mansinam Island has excellent potential as an ecotourism destination, there is still significant room for improvement in community participation. Economically, many opportunities, such as equipment rental and tourist product development, have not been fully utilized. On the environmental conservation side, although awareness has developed, active community participation still needs to be improved. From a social aspect, despite the existence of art and cultural studios, community involvement in promoting and developing local cultural values is still limited. The conclusion of this study is the need to increase community participation in every aspect of ecotourism on Mansinam Island. This includes local economic development, environmental preservation, and the preservation and promotion of local culture. Through increased community participation, Mansinam Island can optimize its potential as a sustainable ecotourism destination and provide more comprehensive benefits to the local community.